2010
DOI: 10.1136/ip.2010.027177
|View full text |Cite
|
Sign up to set email alerts
|

Horse-related facial injuries: the perceptions and experiences of riding schools

Abstract: This study aimed to investigate the perceptions and experiences of New Zealand horse riding schools with regard to horse-related facial injuries. All the riding schools listed in the New Zealand electronic phonebook directory were surveyed by post. The survey questions covered riding schools' perceptions of rider profile, general and facial injury patterns and safety equipment used. The face was perceived to be the most common injury site by only 4% of respondents. Helmets were enforced in only 35% of the scho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(24 citation statements)
references
References 14 publications
1
23
0
Order By: Relevance
“…Findings from employer-derived injury data [4] found that Latino workers were more likely to report horse-related injuries than nonLatinos, which suggests that Latinos are more highly represented in jobs directly involving the horse-which account for most injuries. Our findings support recommendations by other researchers that horse-related PPE should be provided to un-mounted horse workers [9,10,43,45], particularly given drastic reductions in the severity of equestrian injuries that their use has allowed [11,44]. In addition, workers' attitudes toward and perceived availability of PPE should be the subject of future research.…”
Section: Discussionsupporting
confidence: 89%
“…Findings from employer-derived injury data [4] found that Latino workers were more likely to report horse-related injuries than nonLatinos, which suggests that Latinos are more highly represented in jobs directly involving the horse-which account for most injuries. Our findings support recommendations by other researchers that horse-related PPE should be provided to un-mounted horse workers [9,10,43,45], particularly given drastic reductions in the severity of equestrian injuries that their use has allowed [11,44]. In addition, workers' attitudes toward and perceived availability of PPE should be the subject of future research.…”
Section: Discussionsupporting
confidence: 89%
“…14,28 Orbital floor, jaw and zygomatic arch injuries occur in both mounted and un-mounted situations 14,29 Most of the facial injuries reported in another study were soft tissue (56%) with the others being bony. Of those, 58% resulted in fracture.…”
Section: Headmentioning
confidence: 99%
“…Meredith reported only 35% of students wore a helmet when un-mounted. 29 This is perplexing as an un-mounted rider performing tasks around the horse increases the risk of being injured by the horse's head or hoof. Face shields or masks have proven effective in reducing facial injuries in bull riding and have been discussed as a way to reduce the risk of injuries to the front of the skull in traditional equestrian competitions.…”
Section: Headmentioning
confidence: 99%
“…Journal samples from four major Swedish animal hospitals show that the problem exists according to a preliminary survey by the authors. However, there have been studies on human injuries inflicted by horses (Kriss & Kriss, 1997;Meredith & Antoun, 2011;Eckert et al, 2011) with horse kicks accounting for approx. 10% of these injuries (Meredith & Antoun, 2011).…”
Section: Literature and Preliminary Workmentioning
confidence: 99%
“…However, there have been studies on human injuries inflicted by horses (Kriss & Kriss, 1997;Meredith & Antoun, 2011;Eckert et al, 2011) with horse kicks accounting for approx. 10% of these injuries (Meredith & Antoun, 2011). Most of these are attributed to poor handling of horses.…”
Section: Literature and Preliminary Workmentioning
confidence: 99%